Transient Neurologic Deficit without Vascular Pathology Correlates with Reversible Focal Hypoperfusion on Arterial Spin Labeled Perfusion Imaging - Diller, Emily E.; Parker, Jason G.; Ey, Elizabeth H.; Lober, Robert M. (Journal of Pediatric Neurology, 2019)
We present the case of a 16-year-old boy with altered mental status and magnetic resonance imaging demonstrating left hemispheric hypoperfusion without evidence of stroke, based on arterial spin labeling (ASL) and dynamic contrast-enhanced perfusion imaging. Vessel imaging on magnetic resonance angiography and computed tomography angiography, in addition to an echocardiogram, showed no evidence of an embolic source. Electroencephalography showed left posterior temporal slowing. Within 8 hours, he was awake and alert but with receptive aphasia, and within 24 hours his symptoms completely resolved. Repeat ASL perfusion imaging demonstrated complete resolution of the perfusion abnormality, and diffusion imaging revealed no areas of infarct. This report demonstrates the correlation between a transient neurologic deficit and reversible focal hypoperfusion measured by ASL cerebral perfusion.
Keywords: arterial spin labeling; magnetic resonance imaging; focal hypoperfusion